2017
DOI: 10.3762/bjnano.8.174
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-mediated synthesis of magnetic nanoparticles and functionalization with gold quantum dots for theranostic applications

Abstract: Biocompatible superparamagnetic iron oxide nanoparticles (NPs) through smart chemical functionalization of their surface with fluorescent species, therapeutic proteins, antibiotics, and aptamers offer remarkable potential for diagnosis and therapy of disease sites at their initial stage of growth. Such NPs can be obtained by the creation of proper linkers between magnetic NP and fluorescent or drug probes. One of these linkers is gold, because it is chemically stable, nontoxic and capable to link various biomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The increase in band gap in case of ZnO-L-Ala attributes to the bonding between COO group of alanine and ZnO surface causing strain upon NH 3 + group. 28 The lattice strain in L-Ala due to surface bonding between ZnO and -COO is around 0.09 eV as reported in the literature 28 Figure 4C, it can be inferred that ZnO-D-Ala and ZnO-DL-Ala has large crystallite size with less band gap value of 2.85 eV, whereas other ZnO-AA complexes possess small crystallite size with widened band gap than ZnO NRs.…”
Section: Electronic Spectroscopy Analysissupporting
confidence: 65%
“…The increase in band gap in case of ZnO-L-Ala attributes to the bonding between COO group of alanine and ZnO surface causing strain upon NH 3 + group. 28 The lattice strain in L-Ala due to surface bonding between ZnO and -COO is around 0.09 eV as reported in the literature 28 Figure 4C, it can be inferred that ZnO-D-Ala and ZnO-DL-Ala has large crystallite size with less band gap value of 2.85 eV, whereas other ZnO-AA complexes possess small crystallite size with widened band gap than ZnO NRs.…”
Section: Electronic Spectroscopy Analysissupporting
confidence: 65%
“…The peaks at 84.0 eV (4f 7/2 ) and 87.7 eV (4f 5/2 ) corresponds to metallic gold while less intense peaks at 85.58 and 89.47 eV corresponds to Au + . [65] In Figure 4d3, the presence of three types of chorine moieties shows the pristine state of PPy chains in PPy/Cl − . [60] The peaks at 197.…”
Section: Metal Ion Conversion Reactionmentioning
confidence: 99%
“…Patricia et al developed three different lignin nanoparticles which show better stability, biocompatibility, uniform dispersity, ability to load poorly soluble drugs, good cellular interaction and sustained drug release for disease diagnosis and therapy [19]. Jagminas et al reported a novel method to synthesise methionine mediated super paramagnetic Cobalt ferrite nanoparticle linked with gold quantum dots which has promising application in targeted drug delivery [20]. Chen et al inspected a pH-sensitive drug release system for targeting CD44 receptor using doxorubicin conjugated mesoporous silica nanoparticles which exhibited improved drug effectiveness and better stability at functional pH for novel preparation of drug delivery systems [21].…”
Section: Nanoparticlesmentioning
confidence: 99%